Cyprian and the Bishops of Rome: Questions of Papal Primacy in the Early Church. By Geoffrey D. Dunn - Hall, Stuart George (The journal of theological studies, 2008)
The letters of Cyprian form the largest collection of evidence we have for the organization of the Church in the third century. Dunn's study, aimed to clarify the nature and operation of the primacy of the Bishop of Rome at that time, depends chiefly upon them, though other evidence is added. Dunn is confidently fluent in the primary and secondary literature of his subject. His chief finding is that no juridical primacy was known or claimed. For Cyprian Petrine primacy was the position of each bishop in his church, though in Rome a historic origin with Peter's own episcopate was acknowledged, and the greater weight was naturally accorded to the largest church in the West.